1998
DOI: 10.1002/(sici)1097-0185(199810)252:2<229::aid-ar8>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Preganglionic fibers in the rat hypogastric nerve project bilaterally to pelvic ganglia

Abstract: Stimulation of the hypogastric nerve (HGN) often evokes bilateral responses in some pelvic organs. Retrograde labeling studies indicate that axons of postganglionic neurons often cross to the opposite side. However, there is little information available as to whether preganglionic fibers in the HGN have a contralateral projection to pelvic ganglia. A retrograde tracer was injected into the left major pelvic ganglion (MPG) in rats receiving various lesions of preganglionic nerves (HGN and pelvic nerve, PN). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Whole transverse sections were cut on a vibrating tissue slicer (Electron Microscopy Sciences, Fort Washington, PA, USA) at a thickness of 250 μm in ice-cold PBS. These sections were briefly analyzed in a Nikon E600 light microscope equipped for epifluorescent detection of FG through a UV filter, where we confirmed that the pattern of FG fluorescence in SPNs was consistent with previously published studies (Harji et al, 1998) of MPG injection, with no evidence of systemic tracer leakage. Sections were cut to isolate the IML and DCN nuclei for embedding, and then cryo-protected through a graded series of glycerol in PBS, and stored overnight at 4°C in a solution of 30% glycerol.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Whole transverse sections were cut on a vibrating tissue slicer (Electron Microscopy Sciences, Fort Washington, PA, USA) at a thickness of 250 μm in ice-cold PBS. These sections were briefly analyzed in a Nikon E600 light microscope equipped for epifluorescent detection of FG through a UV filter, where we confirmed that the pattern of FG fluorescence in SPNs was consistent with previously published studies (Harji et al, 1998) of MPG injection, with no evidence of systemic tracer leakage. Sections were cut to isolate the IML and DCN nuclei for embedding, and then cryo-protected through a graded series of glycerol in PBS, and stored overnight at 4°C in a solution of 30% glycerol.…”
Section: Methodssupporting
confidence: 86%
“…It is known that some of these neurons, contrary to the standard paradigm of sympathetic projections, actually extend their axons through the spinal chain ganglia and the inferior mesenteric ganglion without synapsing, as they are identifiable through application of retrograde tracers, such as horseradish peroxidase, to the transected stump of the hypogastric nerve (Nadelhaft and McKenna, 1987, Baron and Jänig, 1991). More recently, these neurons have also been traced through the injection of retrograde tracers such as cholera toxin subunit B (Hosoya et al, 1994, Llewellyn-Smith et al, 2005, Ranson et al, 2006) or Fluorogold (Harji et al, 1998, Chang and Havton, 2010) directly into the major pelvic ganglion (MPG) itself, where the parasympathetic preganglionic neurons (PPNs) in the lumbosacral spinal cord also project their axons via the pelvic nerve (Keast, 1995). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ganglia on one side are interconnected by numerous fiber tracts and the majority of inputs from the spinal cord occur ipsilaterally. In addition in some species fiber connections between the right and left pelvic plexuses and the IMGs occur (220, 327, 622) and synaptic interactions between the right and left plexuses have been reported (257). The striated muscle of the external urethral sphincter (EUS) is directly innervated by axons originating from motoneurons in the spinal cord.…”
Section: Peripheral Nervous Systemmentioning
confidence: 99%
“…The vas is innervated by autonomic postganglionic nerve fibers originating primarily from neurons in pelvic ganglia, and to a lesser extent, from neurons in the caudal mesenteric ganglion and sympathetic chain ganglia, and also by sensory nerve fibers arising from dorsal root ganglia (Kaleczyc, 1998; Kihara et al, 1998; Burnstock and Verkhratsky, 2010). In rodents the hypogastric nerve provides bilateral innervation to the vas, and contractile responses can be elicited with hypogastric stimulation from either side (Kihara et al, 1996; Harji et al, 1998). …”
Section: General Structure Of Vas Deferensmentioning
confidence: 99%